PENGARUH FINANCIAL DISTRESS, PERGANTIAN MANAJEMEN DAN UKURAN KAP TERHADAP AUDITOR SWITCHING - Juli Is Manto; Dewi Lesmana Wanda (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2018)
Aim of this research is to examine the effect of financial distress, management turnover and Public Accountant Firm (KAP) size on switching auditors of service companies real estate and property sub-sectors listed on the Indonesia Stock Exchange in 2011-2016. Secondary data is sourced from financial statements, published by the Capital Market on the Indonesia Stock Exchange. The type of research used in this study is testing hypotheses, using purposive sampling method. There are 210 data samples that are used as research objects. This study uses logistic regression analysis to test the hypothesis. The results showed that financial distress and KAP size had a significant effect on switching auditors with a negative coefficient direction, while management change had a significant effect on the auditor switching with a positive coefficient direction. Whereas simultaneously financial distress variables, management turnover and KAP size have a positive and significant influence on the switching auditor.